Root-lesion nematodes of the genus Pratylenchus (Nematoda: Pratylenchidae) from Costa Rica with molecular identification of P. gutierrezi and P. panamaensis topotypes - Zamora, Tatiana (2016)
Root-lesion nematodes of the genus Pratylenchus are among the most damaging nematodes for crop and ornamental plants worldwide. There are about 75 described species in this genus with a wide host range, but a difficult diagnosis because of morphological similarities and overlapping of morphometric characters among species. Four species of Pratylenchus were detected parasitizing cultivated and ornamental plants in Costa Rica: Pratylenchus bolivianus, P. gutierrezi, P. pseudocoffeae, and P. zeae; while P. panamaensis was detected in coffee in the type locality at Panama. The specimens were identified using morphological and molecular methods. Morphometrics and morphology using light and scanning electron microscopy are given for all of them. The presence of P. bolivianus and P. pseudocoffeae are reported for the first time in Costa Rica. The molecular and morphological variability associated with former populations of P. gutierrezi showed that we are in front of complex of species. This has been resolved with the study of topotype populations of P. gutierrezi and P. panamaensis combined with rDNA sequences (D2-D3 expansion segments of 28S and ITS). Our results, including SEM en face view data on topotypes of P. gutierrezi and P. panamaensis demonstrated that both species are almost undistinguishable morphologically, but clearly separated molecularly with D2-D3 expansion segments of 28S (89 % similar, 84 nucleotides and 19 indels) and ITS rDNA (only 36 % coverage with a 88 % similarity value). Consequently, P. gutierrezi and P. panamaensis need to be maintained as different valid taxa. Molecular data on D2-D3 expansion segments of 28S and ITS rDNA of topotypes of P. panamaensis were also coincident (99 % similarity) with root-lesion nematodes parasitizing coffee in Guatemala and Costa Rica, and banana in Madeira, and previously identified as P. gutierrezi (K1-AF170440, K2-AF170441, FR692277, respectively), which need to be considered conspecific with P. panamaensis. These results showed us the necessity of integrative taxonomy in the identification and characterization of Pratylenchus spp.